Evaluating quality of life improvements in endometriosis patients following laparoscopic surgery using EHP-30 scale - Yuyan Guo; Penghui Huang; Chaobin Liu; Zhenna Wang; Yi Wang; Wei Qi; Xi Xie; Zhenhong Wang; Jinna Zhang; Shunhe Lin (Scientific Reports)
Abstract This study aims to evaluate whether laparoscopic surgery enhances health-related quality of life (HRQoL) in endometriosis patients, utilizing the Endometriosis Health Profile-30 (EHP-30) questionnaire. The study also explores the correlations between disease severity, preoperative scores, and the subsequent changes following surgical intervention. This is a prospective observational study. Seventy women undergoing laparoscopic surgery for endometriosis at Fujian Maternity and Child Health Hospital were prospectively recruited. Each participant was assessed using the EHP-30 questionnaire both 4 weeks prior to and 3 months post-surgery to obtain preoperative and postoperative subscale scores. The Wilcoxon signed-rank test was applied to determine the statistical significance of changes in these scores. Spearman’s rank correlation coefficient was employed to explore the relationships between preoperative EHP-30 scores, serum CA125 levels, and intraoperative revised American Society for Reproductive Medicine (rASRM) scores. Statistically significant correlations were further examined using multivariate linear regression analysis to adjust for potential confounders. Laparoscopic surgery resulted in a significant reduction in EHP-30 subscale scores (P ≤ 0.002), indicating a marked improvement in HRQoL among endometriosis patients. Spearman correlation analysis revealed positive correlations between preoperative serum CA125 levels (P = 0.005) and intraoperative rASRM scores with preoperative pain (P = 0.035) and sexual intercourse scores (P = 0.046). Additionally, multivariate linear regression analyses demonstrated that changes in pain scores (ΔPain), control and powerlessness (ΔControl and Powerlessness), and work life (ΔWork Life) were significantly interrelated (P < 0.01). Emotional well-being (ΔEmotional Well-being), control and powerlessness (ΔControl and Powerlessness), and work life (ΔWork Life) also exhibited significant mutual influences (P < 0.01). Furthermore, changes in social support (ΔSocial Support), self-image (ΔSelf-image), and treatment perception (ΔTreatment) were positively correlated (P < 0.01), as were changes in sexual intercourse (ΔSexual Intercourse) and concern about infertility (ΔConcern on Infertility) (P < 0.01). Laparoscopic surgery for endometriosis significantly improves HRQoL by alleviating pain and positively influencing daily functioning and emotional well-being. These findings highlight the critical role of laparoscopic surgery as an effective intervention for enhancing the quality of life in endometriosis patients.